HEALTH SERVICES VIEWED FROM NETWORK GOVERNANCE PERSPECTIVE IN KOLAKA REGENCY, SOUTHEAST SULAWESI - Abdul Sabaruddin; Firdaus Firdaus; Taslim Fait (Sosiohumaniora, 2023)
The complexity of problems in health services, especially the handling of Corona Virus Disease 2019 (COVID-19) requires government strategies and policies. Involving stakeholders through a network governance approach is a government policy in overcoming the spread of COVID-19. The purpose of this study is to provide an overview of local government policies and an explanation of network governance in health services, especially in the handling of COVID-19. The research was conducted in 2022 in Kolaka Regency, Southeast Sulawesi Province. This study uses a qualitative-descriptive research method. Research data was obtained through observation, literature study, interviews and official government websites and the mass media regarding the handling of COVID-19. The results of the study show that the local government policy of Kolaka Regency in handling COVID-19 is by forming a Task Force which involves multi-stakeholders, namely elements of the local government, elements of universities, TNI/Polri, State-owned enterprises (PT Antam and BRI Kolaka), BUMD (Perusda Kolaka, Bank Bahteramas and BPD Kolaka) Private Companies (PT Vale and PT Ceria, and Bank Mandiri), Professional Organizations (IDI Kolaka Regency, Indonesian National Nurses Association of Kolaka Regency, Association of Indonesian Environmental Health Experts, Indonesian Pharmacists Association of Kolaka Regency, and PWI of Kolaka Regency), religion organizations (MUI Kolaka, Gepsultra Klasisi Kolaka), social organizations (RAPI Kolaka, Association of Indonesian Hotels and Restaurants (PHRI) and PMI. The elements involved in the Task Force describe the network governance model. The network governance approach is the right model in public service. This perspective assumes that the actors involved are interdependent, exchange resources and have a clear framework. The focus of the network governance approach which lies on the coordination mechanism is apparently not sufficient in unifying the vision and mission of the actors. However, it must be supported by strong leadership and commitment from each actor.